Influence of a Cereal Rye Cover Crop and Conservation Tillage on the Critical Period for Weed Control in Cotton. (21st December 2018) - Price, Andrew J.; Korres, Nicholas E.; Norsworthy, Jason K.; Li, Steve
Abstract: Cover crops are being increasingly recommended as an integrated approach to controlling glyphosate-resistant Palmer amaranth and other troublesome weeds. Thus, a field experiment was conducted in 2010 through 2012 to evaluate the critical period for weed control (CPWC) in cotton as affected by a cereal rye cover crop and tillage. The management systems evaluated included conventional tillage following winter fallow, conservation tillage (CT) following winter fallow, and CT following a cereal rye cover crop managed for maximum biomass. Throughout most of the growing season, weed biomass in cereal rye cover crop plots was less than the CT winter-fallow system in both years and less than both CT winter fallow and conventional tillage in 2012. The CPWC was shortest in 2010 following conventional tillage; however, in 2012, production system influences on CPWC were less. The presence of the rye cover crop delayed the critical timing for weed removal (CTWR) approximately 8 d compared with fallow treatment both years, while conventional tillage delayed CTWR about 2 wk compared with winter fallow. Relative yield losses in both years did not reach the 5% threshold limit until about 2 wk after planting (WAP) for CT following winter fallow, 3 WAP for CT following a cover crop, and 3.5 WAP following conventional tillage. Thus, CT following winter fallow should be avoided to minimize cotton yield loss.